2008
DOI: 10.1007/s10853-008-2522-4
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure development in Nb3Sn(Ti) internal tin superconducting wire

Abstract: The authors have studied the phase formation sequences in a Nb 3 Sn 'internal tin' process superconductor. Heat treatments were performed to convert the starting materials of tin, Ti-Sn, copper and niobium, to bronze and Nb 3 Sn. Specimens were quenched at different points of the heat treatment, followed by metallography to identify the phases present and X-ray microtomography (XMT) to investigate the void volume and distribution. An unexpected observation of the microstructure development was the uphill diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…The reason for this is that the processing of high-temperature oxide compounds in the form of flexible compounds such as wires or coils is still very difficult to achieve due to their brittle, salt-like structure. Thus, intermetallic compounds are usually used as superconducting magnets and wires [2][3][4]. Recently, this special interest has gravitated towards intermetallic superconductors based on heavy 5d transition metals such as Ir and Pt which are chracterised by large spin orbit coupling (SOC).…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is that the processing of high-temperature oxide compounds in the form of flexible compounds such as wires or coils is still very difficult to achieve due to their brittle, salt-like structure. Thus, intermetallic compounds are usually used as superconducting magnets and wires [2][3][4]. Recently, this special interest has gravitated towards intermetallic superconductors based on heavy 5d transition metals such as Ir and Pt which are chracterised by large spin orbit coupling (SOC).…”
Section: Introductionmentioning
confidence: 99%
“…Затем сплавы и интерметаллические соединения [2,3], их физические [4,5] и химические свойства исследовали многие авторы [6,7]. Интерес к сплавам ниобия с оловом связан со сверхпроводящими свойствами интерметаллических соединений, особенно металлида Nb 3 Sn [8][9][10][11].…”
Section: Introductionunclassified
“…Thus, intermetallic superconductors are commonly used for technological applications. In superconducting magnets and wires most popular are Nb 3 Sn and Nb 3 Ge compounds with A15 structure [3]. A few years ago it has been shown that BaSn 5 has similar electronic properties to the A15 superconductors [4].…”
Section: Introductionmentioning
confidence: 99%